2016
DOI: 10.1016/j.bbr.2015.11.035
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D1 receptor activation improves PCP-induced performance disruption in the 5C-CPT by reducing inappropriate responding

Abstract: Attentional deficits contribute significantly to the functional disability of schizophrenia patients. The 5-choice continuous performance test (5C-CPT) measures attention in mice, rats, and humans, requiring the discrimination of trial types that either require a response or the inhibition of a response. The 5C-CPT, one version of human continuous performance tests (CPT), enables attentional testing in rodents in a manner consistent with humans. Augmenting the prefrontal cortical dopaminergic system has been p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 85 publications
0
13
0
Order By: Relevance
“…We have also previously shown that targeting dopamine D 1 receptors ameliorates the effects of scPCP treatment in NOR, reversal learning and the 5 choice continuous performance test (McLean et al, 2009;Barnes et al, 2016), further implicating the role of dopamine in prefrontal-based cognitive tasks.…”
Section: Introductionmentioning
confidence: 78%
“…We have also previously shown that targeting dopamine D 1 receptors ameliorates the effects of scPCP treatment in NOR, reversal learning and the 5 choice continuous performance test (McLean et al, 2009;Barnes et al, 2016), further implicating the role of dopamine in prefrontal-based cognitive tasks.…”
Section: Introductionmentioning
confidence: 78%
“…Attentional deficits contribute significantly to functional disability of patients with schizophrenia among other patient populations (Green et al, 2004; Marder and Fenton, 2004). In a previous investigation, pro‐attentive properties of SKF38393 were determined in rats with phencyclidine‐altered attentional performance (Barnes et al, 2016). More akin to our study design and attentional behavioural assay, a previous study determined the effect of local infusions of SKF38393 on attentional performance in rats selected for high and low 5‐CSRTT performance (Granon et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Acute administration of NMDA receptor antagonists, such as ketamine, phencyclidine (PCP) and dizocilpine, has been shown to negatively impact on domains of executive function in rodents, impairing cognitive flexibility (de Bruin et al, ; Gastambide et al, ) and disrupting attentional processing (Amitai and Markou, ; Barnes et al, ; Thomson et al, ). Acute NMDA receptor antagonist administration also negatively affects other cognitive domains impairing spatial reference learning and memory (for review, see Morris, ; Duan et al, ; Ihalainen et al, ), short‐term object recognition memory (Cloke and Winters, ; Rajagopal et al , ), associative memory (as assessed in the paired associates learning task, Kumar et al, ; Lins et al, ) and episodic learning and memory (Bast et al, ) in rodents.…”
Section: Evidence From Pharmacological Studies In Rodentsmentioning
confidence: 99%
“…These effects on plasticity include modifications in the function of non‐glutamatergic neurotransmitter systems (Jentsch et al, ; Lindefors et al, ), including the function of parvalbumin‐positive (PV+) GABAergic interneurons (Bygrave et al, ), changes in synaptic plasticity (Nomura et al, ), alterations in regional neuronal activity, including prefrontal cortex (PFC) hypofunction (Dawson et al, ), and altered brain network connectivity (see later discussion). In these studies, prolonged NMDA receptor antagonism has been shown to induce deficits in cognitive flexibility (Dawson et al, ; McLean et al, ), attentional processing (Thomson et al, ; Barnes et al, ), spatial reference learning and memory (Didriksen et al, ), working memory (Seillier and Giuffrida, ) and short‐term object recognition memory (Pyndt Jorgensen et al, ; Horiguchi et al, ; Rajagopal et al, ). While the translational relevance of some of these behavioural tests to aspects of human cognition is questionable (Kas et al, ; Pratt et al, ; Pryce and Seifritz, ), the overall findings indicate a central role for the NMDA receptor in a broad range of cognitive processes.…”
Section: Evidence From Pharmacological Studies In Rodentsmentioning
confidence: 99%